2021
DOI: 10.1097/ju.0000000000001933
|View full text |Cite
|
Sign up to set email alerts
|

Suture-Free Sealing of Tunical Defect with Collagen Fleece after Partial Plaque Excision in 319 Consecutive Patients with Peyronie's Disease: The Sealing Technique

Abstract: Purpose: We describe the sealing technique with collagen fleece in patients with advanced Peyronie's disease (PD) and provide the prospective long-term outcomes. Materials and Methods: We performed a multicenter cohort study in patients with preserved erectile function and stable PD that precluded sexual intercourse. All patients underwent partial plaque excision with collagen fleece grafting. The applied technique is explained through a high-quality video accompanied by relevant animations. After hospital dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Multiple literature reviews reported that these grafts are comparable regarding clinical outcomes; however, the heterogeneity of the series published makes it difficult to conclude ( 1 - 3 , 41 - 43 ). Nevertheless, TachoSil stands out as an operative time saver compared to others ( 3 , 36 , 37 , 44 , 45 ). Due to its ready availability, sutureless application, and hemostatic effect, TachoSil gained popularity in PD surgery.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Multiple literature reviews reported that these grafts are comparable regarding clinical outcomes; however, the heterogeneity of the series published makes it difficult to conclude ( 1 - 3 , 41 - 43 ). Nevertheless, TachoSil stands out as an operative time saver compared to others ( 3 , 36 , 37 , 44 , 45 ). Due to its ready availability, sutureless application, and hemostatic effect, TachoSil gained popularity in PD surgery.…”
Section: Discussionmentioning
confidence: 85%
“…Early experience with TachoSil patching and plaque incision or excision in patients with an erection hardness score of a mean of 3.4 showed that the score decreased significantly to 2.6 ( 31 ). In subsequent larger and multicenter clinical studies, the TachoSil patch, even with a relatively large size, was associated with nearly ~ 16% de novo erectile dysfunction ( 36 , 37 ). The reported mean longitudinal length of TA defect is 21.9 mm (range, 5–40) for plaque excision ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies by Hatzchristodoulou et al . 12 13 reported an average increase in penile length of 0.7 cm and 1.1 cm, respectively, after TachoSil surgery. However, a study by Horstmann et al .…”
Section: Resultsmentioning
confidence: 98%